Innovative zero-valent cobalt decoration on MIL-88 A(Fe)@β-CD for high-efficiency and reusable cr(VI) removal - Eman M. Abd El-Monaem; Nouf Al Harby; Mervette El Batouti; Abdelazeem S. Eltaweil (Scientific Reports)
Abstract Herein, the magnetic ZVCo-MIL-88 A(Fe)@β-CD composite was fabricated via post-synthetic decoration of MIL-88 A(Fe)@β-CD with ZVCo to produce a magnetic efficient adsorbent for Cr(VI) removal. The experimental findings denoted that the ZVCo decoration boosted the adsorption capability of MIL-88 A(Fe)@β-CD, where the adsorption % of Cr(VI) improved from 73.07 to 94.02% after its decoration with 10 wt% of ZVCo. Furthermore, the ZVCo decoration ameliorated the recycling feature of MIL-88 A(Fe)@β-CD since the removal % of Cr(VI) by MIL-88 A(Fe)@β-CD and ZVCo-MIL-88 A(Fe)@β-CD reached 27.24 and 84.98%, respectively. The optimization experiments of the Cr(VI) ions clarified that the higher adsorption % fulfilled 94.02% at pH = 3, using ZVCo-MIL-88 A(Fe)@β-CD dosage = 0.5 g/L, Cr(VI) concentration = 50 mg/L, and at room temperature. Notably, the concentration of the adsorbed Cr(VI) brings off the equilibrium stage within an hour, implying the fast adsorption property of ZVCo-MIL-88 A(Fe)@β-CD. The kinetic and isotherms assessments denoted the contribution of the physical and chemical adsorption pathways in adsorbing the Cr(VI) species onto ZVCo-MIL-88 A(Fe)@β-CD. In addition, the XPS spectra and zeta potential results supposed that the process inside the Cr(VI)/ZVCo-MIL-88 A(Fe)@β-CD system proceeded through reduction reaction, coordination bonds, electrostatic interactions, and pore-filling mechanisms.